The Effect of Hybrid Learning and Achievement Motivation on Civics Learning Outcomes for Class 6 Students at SDN Kaliasin I Surabaya - Siti Anik Handayani; Ahmad Noor Fatirul; Djoko Adi Walujo (Institute of Computer Science (IOCS), 2022)
The purpose of this study was to examine the use of Hybrid Learning and achievement motivation on Student Civic Education Learning Outcomes. This study used a 2X2 factorial quasi-experimental design. The research data were collected using the questionnaire method and the test method. Then the data were analyzed using the two-way ANOVA statistical analysis technique. The research population was all students of class VI SDN Kaliasin I Surabaya. In this study, the instruments used were study questionnaires and PPKN learning outcomes tests. This questionnaire uses a Likert scale. Data collection methods commonly used in a study are: tests, interviews, questionnaires, and observations. Based on the research, the following results were obtained (1) There is a difference in the effect of Hybrid Learning and Online Learning on student Civic Education learning outcomes. PPKN learning using Hybrid Learning produces student PPKN learning outcomes better than Online Learning, (2) There are differences in PPKN learning outcomes for students who have high achievement motivation and students who have low achievement motivation. Students who have a high level of achievement motivation produce better PPKN learning outcomes than students who have a low level of achievement motivation, and (3) There is an interaction between learning models and achievement motivation on PPKN learning outcomes. Civics learning using Hybrid Learning on students who have a high level of achievement motivation have better PPKN learning outcomes than students who have a low level of achievement motivation. Based on the results of this study, it was concluded that using Hybrid Learning and achievement motivation could improve student learning outcomes of PPKN at SDN Kaliasin I Surabaya. The implication of this research is that Hybrid Learning can be used as a way to improve student learning outcomes in Civics.